Effluent syntaxin3 from dying cells affords protection against apoptosis in epidermal keratinocytes. Issue 12 (December 2013) - Miyazaki, Takafumi; Kadono, Nanako; Konishi, Yoshihiro; Hagiwara, Natsumi; Maekubo, Kenji; Hirai, Yohei
Abstract Ultra‐violet B (UVB)‐induced oxidative stress crucially perturbs the epidermal homeostasis, and the skin is endowed with protective mechanisms to take action against such damage. Here, we show the possible involvement of t‐SNARE protein syntaxin3, a membrane fusion mediator of cytoplasmic vesicles, and which is released from dying keratinocytes, to play a role in this response. UVB irradiation, which generates reactive oxidative stress in cells, was shown to lead to the keratinocyte cell death accompanied by a release of cytoplasmic syntaxin3. We found that such extracellularly sourced syntaxin3 completely blocked the processing of a crucial effector for apoptotic cell death, caspase‐3, and thus facilitated the survival of keratinocytes damaged by oxidative stress. These results demonstrate the latent prosurvival function of syntaxin3 and underline the importance of intracellular molecular elements for the maintenance of homeostasis in epidermal keratinocytes.